An ab initio study of carboxylated graphene and black - and blue - phosphorene - Tonel, Mariana Zancan; Ledur, Cristian Mafra; Lara, Ivi Valentini; Silva, Ivana Zanella da; Fagan, Solange Binotto (Disciplinarum Scientia | Naturais e Tecnológicas, 2017)
This work presents a first-principles study, based on Density Functional Theory calculations, on the structural, electronic and magnetic properties of black and blue phosphorene as well as of graphene functionalized with carboxylic group. The binding distance between phosphorene and carboxyl group assumes a higher value than that on graphene because of phosphorus atomic radius. Carboxyl also pulls slightly closer the graphene and black phosphorene functionalized atom, while blue phosphorene atom is pushed away. Unlike graphene, black and blue phosphorene have not shown relevant spin polarization. These results could help to understand the nanomaterials properties for a new route for the development of biosensors and, regarding to the phosphorenes, interesting properties with many potential applications that can be developed in the sense of the nanobiotechnology field.